2008
DOI: 10.2203/dose-response.07-008.rodgers
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Adaptive Response to Environmental Exposures at Chernobyl

Abstract: h The genetic consequences resulting from environmental exposure to ionizing radiation have a significant impact on both radiation regulatory policies and the comprehension of the human health risks associated with radiation exposure. The primary objectives of the study were to assess 1) genotoxicity of exposure to radiation as a function of absorbed dose and dose rate, and 2) induction of a radio-adaptive response following a priming dose at varying dose rates. Results demonstrated that sub-acute environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Exposure experiments on rats have been carried out at the Chernobyl accident site (Rodgers and Holmes 2008). Under a variety of conditions, a pre-dose of 10 cGy was given at various dose rates up to 24 hours before a challenge dose of 1.5 Gy.…”
Section: Brief Reviewmentioning
confidence: 99%
“…Exposure experiments on rats have been carried out at the Chernobyl accident site (Rodgers and Holmes 2008). Under a variety of conditions, a pre-dose of 10 cGy was given at various dose rates up to 24 hours before a challenge dose of 1.5 Gy.…”
Section: Brief Reviewmentioning
confidence: 99%
“…3 ), later revised to 100 mGy in the UNSCEAR 2013 report 4 . Indeed, very few animal studies have investigated the effects of continuous chronic LDR radiation at below 6 mGy/h 5 6 7 8 9 , likely due to the limited number of facilities allowing long term in vivo exposure at continuous LDR. This challenge was recognised by the European platform MELODI (Multidisciplinary European Low Dose Initiative) dedicated to low dose radiation risk research ( http://www.melodi-online.eu/ ).…”
mentioning
confidence: 99%
“…At U. C. Davis (Goldberg, et al 2004) en vivo genetic activation experiments were performed on healthy human skin plugs and resulted in similar protective results for the cellular adaptive response to a low radiation dose. Rodgers and Holmes (2008) showed that a low dose (~ 100 mSv) delivered to mice at a very low dose rate over several weeks caused little detectable damage over the control presumably because the cell repair mechanisms had sufficient time to act. The same low dose delivered at a high rate, over ~20 minutes, caused measurable damage.…”
Section: Brief Reviewmentioning
confidence: 99%
“…Rodgers and Holmes (2008) showed that a low dose (∼100 mSv) delivered to mice at a very low dose rate over several weeks caused little detectable damage over the control presumably because the cell repair mechanisms had sufficient time to act. The same low dose delivered at a high rate, over ∼20 minutes, caused measurable damage.…”
Section: Brief Reviewmentioning
confidence: 99%